2011
DOI: 10.1002/jnr.22647
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and pathway analysis of the superior temporal cortex and anterior prefrontal cortex in schizophrenia

Abstract: The molecular basis of schizophrenia is poorly understood; however, different brain regions are believed to play distinct roles in disease symptomology. We have studied gene expression in the superior temporal cortex (Brodmann area 22; BA22), which may play a role in positive pathophysiology, and compared our results with data from the anterior prefrontal cortex (BA10), which shows evidence for a role in negative symptoms. Genome-wide mRNA expression was determined in the BA22 region in 23 schizophrenics and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 47 publications
(54 reference statements)
3
55
0
Order By: Relevance
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…We analysed data from seven, published, microarray‐based studies of age‐related changes in RNA expression (Barnes et al, 2011; Berchtold et al, 2008; Colantuoni et al, 2011; Kang et al, 2011; Lu et al, 2004; Maycox et al, 2009; Somel et al, 2010, 2011 ). The data came from 22 different brain regions, and the ages of the donors ranged from 20 to 106 years (Figure 1a and Supporting Information Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen publicly available microarray data sets were used in this study (Table  1): four data sets on the developing human cortices (GSE13564 [31], GSE25219 [33], GSE11512 [34], GSE37721 [94]), five on the schizophrenic cortices (GSE21138 [32], GSE17612 [36], GSE12649 [35], GSE53987, GSE21935 [95]), two on developing mouse cortex or cells (GSE17806 [37], GSE9566 [38], GSE4675 [96]), one on the medial frontal cortex (MFC) of the schizophrenia mouse model Shn-2 KO mice (GSE42775 [11]), and two on the frontal cortices of rodents treated with antipsychotic drug (GSE45229 [97], GSE2547 [98]). Patient demographics have been previously described in detail [32,35,36,95].…”
Section: Methodsmentioning
confidence: 99%
“…In particular, at BA 22, the vast majority of abnormally expressed genes referred to key autophagy genes (i.e., BECN1 , ULK2 , ATG3 ), which were significantly down-regulated compared with controls [249]. A few months later, another transcriptomic study reported a BA 22-specific down-regulation in several autophagy-related genes, thus strengthening the link between impaired autophagy and schizophrenia positive symptoms [252]. Furthermore, the transcriptional analysis performed on the very same post-mortem samples demonstrated no substantial changes in the mRNA levels of the above-mentioned autophagy-related genes within the anterior prefrontal cortex (BA 10), which is mainly involved in schizophrenic negative symptoms and cognitive dysfunction, thus reinforcing the involvement of an impaired autophagy in mediating positive symptoms.…”
Section: A Step Forward About a Role Of Autophagy In The Pathophysmentioning
confidence: 99%